2010
DOI: 10.1002/cbdv.200900041
|View full text |Cite
|
Sign up to set email alerts
|

Habitat‐Dependent Variations in Berberine Content of Berberis asiaticaRoxb. ex. DC. in Kumaon, Western Himalaya

Abstract: The variation of the berberine content in roots and stem bark of Berberis asiatica with altitude and edaphic conditions in the western Himalaya was estimated by HPLC. The comparative assessment revealed a significantly higher berberine content in roots than in stem barks. Moreover, the berberine content varied significantly with altitude and edaphic conditions both in root and stem bark samples. The populations growing at low altitude contained significantly more berberine than the ones growing at high altitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 12 publications
2
27
0
2
Order By: Relevance
“…Jatrorrhizine was detected in the M. borealis leaf along with magnoflorine, which was also present in the leaves of B. aristata and B. asiatica. B. aristata and B. asiatica had the highest intensity of berberine in their roots relative to stem, and this observation is in accordance with the results reported by Andola and Gaira et al (2010).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Jatrorrhizine was detected in the M. borealis leaf along with magnoflorine, which was also present in the leaves of B. aristata and B. asiatica. B. aristata and B. asiatica had the highest intensity of berberine in their roots relative to stem, and this observation is in accordance with the results reported by Andola and Gaira et al (2010).…”
Section: Resultssupporting
confidence: 92%
“…The peak at m/z 355.1029 [M+H] + corresponds to chlorogenic acid (C 16 H 18 O 9 ) and was detected and recently reported from B. petiolaris by Singh et al (2014). As reported in the literature, berberine is mostly present in the root and the rhizome of the plants (Cromwell 1933;Greathouse & Watkins 1938;Andola and Gaira et al 2010). However, berberine was also identified in B. aristata leaf, which is the first report for this observation.…”
Section: Resultsmentioning
confidence: 59%
“…In addition, Berberine 155 increases the activity of antioxidant enzymes both in vitro and in vivo [81][82][83] peroxidase, as well as glutathione S-transferase in azoxymethane- 165 induced carcinogenic rats [81]. Another study showed that 166 Berberine restores the activity of superoxide dismutase in rats 167 with [115]. Berberis 243 croatica is reported as a novel source of Berberine [116].…”
mentioning
confidence: 99%
“…In the literature, there are various reports regarding the total alkaloid content of dry roots. For instance, B. thunbergii (3.47%) and B. vulgaris (2.22%) [31] show lower percentages than those found in B. microphylla, which may be due to the content of berberine, which is the main alkaloid, varying considerably with altitude and soil conditions for the root [31][32][33]. Total flavonoids were reported as mg equivalents of quercetin.…”
Section: Quantitative Analysismentioning
confidence: 99%